ANNIVERSARY ARTICLE: A Perspective on “Asymmetric Information, Incentives and Intrafirm Resource Allocation” - Rajan, Madhav V.; Reichelstein, Stefan (Management Science, 2004)
The paper “Asymmetric Information, Incentives and Intrafirm Resource Allocation,” by Harris, Kriebel, and Raviv, was published in the June 1982 issue of Management Science. In this article, written as part of this journal's 50-year anniversary celebration, we highlight the significance of the Harris et al. paper for research in managerial accounting. We first formulate and solve a continuous version of the Harris et al. model to illustrate the key assumptions and findings of their paper. We then review several strands of the resource-allocation literature in managerial accounting that have taken their inspiration, either directly or indirectly, from the work of Harris et al.